Concurrent Exposure of Neutralizing and Non-neutralizing Epitopes on a Single HIV-1 Envelope Structure - Ray, Krishanu; Mengistu, Meron; Orlandi, Chiara; Pazgier, Marzena; Lewis, George K.; DeVico, Anthony L. (Frontiers in Immunology, 2019)
The trimeric envelope spikes on the HIV-1 virus surface initiate infection and comprise key targets for antiviral humoral responses. Circulating virions variably present intact envelope spikes, which react with neutralizing antibodies; and altered envelope structures, which bind non-neutralizing antibodies. Once bound, either type of antibody can enable humoral effector mechanisms with the potential to control HIV-1 infection in vivo. However, it is not clear how the presentation of neutralizing versus non-neutralizing epitopes defines distinct virus populations and/or envelope structures on single particles. Here we used single-virion fluorescence correlation spectroscopy (FCS), fluorescence resonance energy transfer (FRET) and two-color coincidence FCS approaches to examine whether neutralizing and non-neutralizing antibodies are presented by the same envelope structure. Given the spatial requirements for donor-acceptor energy transfer (≤ 10 nm), FRET signals generated by paired neutralizing and non-neutralizing fluorescent Fabs should occur via proximal binding to the same target antigen. Fluorescent-labelled Fabs of the neutralizing anti-gp120 antibodies 2G12 and b12 were combined with Fabs of the non-neutralizing anti-gp41 antibody F240, previously thought to mainly bind gp41 “stumps”. We find that both 2G12-F240 and/or b12-F240 Fab combinations generate FRET signals on multiple types of virions in solution. FRET efficiencies position the neutralizing and non-neutralizing epitopes between 7.1 to 7.8 nm apart; potentially fitting within the spatial dimensions of a single trimer-derived structure. Further, the frequency of FRET detection suggests that at least one of such structures occurs on the majority of particles in a virus population. Thus, there is frequent, overlapping presentation of non-neutralizing and neutralizing epitope on freely circulating HIV-1 surfaces. Such information provides a broader perspective of how anti-HIV humoral immunity interfaces with circulating virions.